UPAYA AUSTRALIA DALAM MENANGANI MASALAH PERDAGANGAN MANUSIA DI KAWASAN PASIFIK SELATAN MELALUI KERJA SAMA FORUM BALI PROSES (2013 – 2019) - Ahmad Khoirul Umam; Putri, Shella (Paradigma POLISTAAT: Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
Every year, thousands of people, especially women and children, are victims of human trafficking who are sexually exploited or forced labor, no country is immune to this crime, many countries are sources of trafficked persons, transit points or destinations for trafficking in persons. Australia, which is geographically close to the South Pacific, makes Australia a destination country for trafficking in persons across countries and the South Pacific as a source country. To overcome this problem, Australia is making efforts through the National Action Plan program and the Bali Process regional cooperation forum to address the problem of human trafficking in the South Pacific region. The purpose of writing this article is to look at the issues of human trafficking that occurred in the South Pacific region during the 2013-2019 period and how Australia's efforts and obstacles in carrying out the National Action Plan program and the Bali Process forum to overcome these problems. This article uses Neoliberalisme theory to analyze Australia's efforts through cooperation with various other related actors to address human trafficking in the South Pacific through the Bali Process forum. The results of this study indicate that although it cannot completely eliminate trafficking in persons, the efforts made by Australia have resulted in programs to prevent, detect and protect victims of human trafficking in the region, as well as the creation of cooperation rules through the Bali Process forum that can suppress the development of trafficking in the South Pacific region.